2020
DOI: 10.1038/s41467-020-14326-9
|View full text |Cite
|
Sign up to set email alerts
|

Exchange biased anomalous Hall effect driven by frustration in a magnetic kagome lattice

Abstract: Co 3 Sn 2 S 2 is a ferromagnetic Weyl semimetal that has been the subject of intense scientific interest due to its large anomalous Hall effect. We show that the coupling of this material's topological properties to its magnetic texture leads to a strongly exchange biased anomalous Hall effect. We argue that this is likely caused by the coexistence of ferromagnetism and spin glass phases, the latter being driven by the geometric frustration intrinsic to the Kagome network of magnetic ions.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
69
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(81 citation statements)
references
References 18 publications
10
69
0
Order By: Relevance
“…Only a fraction of the spin folds is repolarized upon a reverse field sweep, resulting in the shifted hysteresis loop. This explanation has similarities to what has been proposed in canonical spin glasses, 42,44 but with a key distinction. In the case of canonical spin glasses, the first field-intercept of the hysteresis loop is independent of the annealing field, which has been interpreted as arising from the introduction of a rigid chiral spin texture in the material, even in the presence of a small magnetic field.…”
Section: ■ Resultssupporting
confidence: 81%
“…Only a fraction of the spin folds is repolarized upon a reverse field sweep, resulting in the shifted hysteresis loop. This explanation has similarities to what has been proposed in canonical spin glasses, 42,44 but with a key distinction. In the case of canonical spin glasses, the first field-intercept of the hysteresis loop is independent of the annealing field, which has been interpreted as arising from the introduction of a rigid chiral spin texture in the material, even in the presence of a small magnetic field.…”
Section: ■ Resultssupporting
confidence: 81%
“…Exchange bias (EB), on the other hand, is also an outcome of such competing interactions. Conventional exchange bias (CEB) manifests itself as a lateral shift in the hysteresis loop, resulting in asymmetric coercive fields, when the sample is cooled under an external magnetic field [5,6]. In recent years, large EB after zero-field cooling from the paramagnetic state, dubbed ZFC EB, was reported in a handful of materials such as Ni-Mn-In bulk alloys [7], Mn 2 PtGa [8,9], and La 1.5 Sr 0.5 CoMnO 6 [10,11], where the ZFC EB effect is rooted in the FM unidirectional anisotropy formed at the interface between different magnetic phases during the initial magnetization process.…”
Section: Introductionmentioning
confidence: 99%
“…1(a)]. Despite the wealth of reports on the topology of the electronic bands [9][10][11][12][13][14][15][16][17][18][19][20][21][22], two fundamental questions regarding the magnetic order of the Co sublattice remain unresolved.…”
mentioning
confidence: 99%
“…The second question concerns the origin of an anomaly observed in the vicinity of T A 125 K in magnetic, transport and optical measurements [10,[24][25][26][27][28]. In measurements of the Hall resistivity, Lachman et al found that the anomaly becomes extremely sharp and discontinuous when the sample is cooled in a field and measurements performed on warming in zero field (FC-ZFW) [14]. Very recently, magneto-optical Kerr effect (MOKE) studies of Co 3 Sn 2 S 2 discovered that this sharp transition is concomitant with a transformation in which a single magnetic domain in a field-cooled sample will spontaneously break up into many smaller domains [19,21].…”
mentioning
confidence: 99%